Metabolic alterations and cellular responses to β-Hydroxybutyrate treatment in breast cancer cells - Fulman-Levy, Hadas; Cohen-Harazi, Raichel; Levi, Bar; Argaev-Frenkel, Lital; Abramovich, Ifat; Gottlieb, Eyal; Hofmann, Sarah Ulrike; Koman, Igor; Nesher, Elimelech (Cancer & metabolism, 2024)
The ketogenic diet (KD), based on high fat (over 70% of daily calories), low carbohydrate, and adequate protein intake, has become popular due to its potential therapeutic benefits for several diseases including cancer. Under KD and starvation conditions, the lack of carbohydrates promotes the production of ketone bodies (KB) from fats by the liver as an alternative source of metabolic energy. KD and starvation may affect the metabolism in cancer cells, as well as tumor characteristics. The aim of this study is to evaluate the effect of KD conditions on a wide variety of aspects of breast cancer cells in vitro. Using two cancer and one non-cancer breast cell line, we evaluate the effect of β-hydroxybutyrate (βHb) treatment on cell growth, survival, proliferation, colony formation, and migration. We also assess the effect of KB on metabolic profile of the cells. Using RNAseq analysis, we elucidate the effect of βHb on the gene expression profile. Significant effects were observed following treatment by βHb which include effects on viability, proliferation, and colony formation of MCF7 cells, and different effects on colony formation of MDA-MB-231 cells, with no such effects on non-cancer HB2 cells. We found no changes in glucose intake or lactate output following βHb treatment as measured by LC-MS, but an increase in reactive oxygen species (ROS) level was detected. RNAseq analysis demonstrated significant changes in genes involved in lipid metabolism, cancer, and oxidative phosphorylation. Based on our results, we conclude that differential response of cancer cell lines to βHb treatment, as alternative energy source or signal to alter lipid metabolism and oncogenicity, supports the need for a personalized approach to breast cancer patient treatment.